A Chitosan Coating Containing Essential Oil from Origanum vulgare L. to Control Postharvest Mold Infections and Keep the Quality of Cherry Tomato Fruit - Barreto, Tainá A.; Andrade, Sonalle C. A.; Maciel, Janeeyre F.; Arcanjo, Narciza M. O.; Madruga, Marta S.; Meireles, Bruno; Cordeiro, Ângela M. T.; Souza, Evandro L.; Magnani, Marciane (Frontiers in Microbiology, 2016)
The efficacy of an edible chitosan coating (CHI; 4 mg/mL) and Origanum vulgare L. essential oil (OVEO; 1.25 µL/mL) for maintaining the quality of cherry tomato fruit during storage at room (25 °C; 12 days) and cold (12 °C; 24 days) temperatures was assessed. CHI and OVEO in combination showed in vitro fungicidal effects against R. stolonifer and Aspergillus niger. CHI-OVEO coating reduced the incidence of black mold and soft rot caused by these fungi in artificially contaminated cherry tomato fruit during storage at both temperatures by more than. CHI-OVEO coating delayed the appearance of the first visible signs of black mold and soft rot in artificially contaminated cherry tomato fruit stored at room temperature by six days and by more than nine days in those stored at cold temperature. At the end of storage at room and cold temperature fruit coated with CHI-OVEO showed higher firmness ( > 2 N/mm) and lower weight loss ( > 2 %) compared to uncoated tomato fruit. CHI-OVEO coating delayed the decrease of lycopene, ascorbic citric acid, glucose and fructose during the storage time assessed at room or cold temperatures. The increase of catechin, myricetin, caffeic and syringic acids was higher (1 - 9 mg/g) in cherry tomato fruit coated with CHI-OVEO compared to uncoated fruit during the storage at both temperatures studied. CHI-OVEO coating is a feasible treatment for maintaining the storage quality of cherry tomato fruit.